E-HKBS paperless patient record system - Kevin Adam, Duyanan (University Malaysia Sarawak (UNIMAS), 2005)
Hospital Kota Belud, Sabah (HKBS) was first built in 1946. Generally it can be considered as an old hospital, but now HKBS has made a lot of improvement in their buildings structure, numbers of staffs, number of patients and beds and so forth. However, HKBS currently is still using the old method that is using paper as theri patients' records.